Dampak Inovasi Teknologi terhadap Efisiensi Biaya dan Daya Saing Perusahaan di Indonesia - Etty Zuliawati Zeed; Ayu Nur Hikmah; Selvi Bayu S; Elena Rahayu; Windri H. Ayuni (BADAN PENERBIT STIEPARI PRESS, 2025)
This study looks at the connection between cost effectiveness, the health of Indonesian company, and technical improvements. The financial statements of 150 publicly traded firms that were listed on the Indonesian Stock Exchange between 2019 and 2023 are the source of this data. Because of the scale of the technological investment and the consistency of the data, samples are chosen via purposeful sampling. Analysis is done using structural persamaan models and panel regression. The findings show that improvements in technology boost daya saing and biaya efficiency (β = 0,647, p < 0,01). The operational biaya ratio for banks and telecommunications businesses was 8.9%, while the aset laba ratio was 14.6%, based on the correlation between financial and technological investment. The study's findings support the strategic notion that technology can provide a competitive advantage. This study also offers helpful advice regarding the importance of funding technological research and development for corporate strategy. Penelitian menghadapi kendala as a result of the utilization of secondary data, which is insufficient to accurately depict the qualitative features of the technology in question.